Trends in the enterovirus surveillance in Oslo, Norway before and during the COVID-19 pandemic - Dudman, Susanne; Klundby, Ingvild; Øverbø, Joakim; Numanovic, Sanela; Nilsen, Mariann; Lind, Andreas; Holberg-Petersen, Mona; Landaas, Elisabeth Toverud (Frontiers in Virology, 2024)
Enteroviruses have the potential to cause both high morbidity and mortality especially in children.High season in Norway is between August and November, but this seasonality was interrupted by the COVID-19 pandemic.Methods:In this study, we describe the enterovirus surveillance in Norway before and during the COVID-19 pandemic including the years from the start of 2016 until the end of 2022. Screening of enterovirus was performed by both laboratory developed methods and FilmArray® ME Panel. Relevant samples were typed,Typing was done in mostly samples by VP1 sequencing.Seventy-four percent of all cases occurred in infants under five years of age. A significant reduction in positive cases was observed during the peak years of the COVID-19 pandemic compared to the years before. Pre-pandemic, a wide range of types from all four enterovirus species were detected. During the years with COVID-19 infection control measures, significantly fewer enterovirus types were found along with a substantial reduction in the detection rate.Enterovirus surveillance discovered a large amount of different types mainly affecting infants. The positivity rate was markedly reduced during the pandemic in 2020-2022 and fewer types occurred.